UNHCR AND ROHINGYA REFUGEES IN ACEH: HUMANITARIAN INTERVENTIONS AMIDST COORDINATION AND SUSTAINABILITY CHALLENGES - Sutrisno, Andri; Wendra, Muhammad; Annas, Muhammad (Jurnal Hukum Progresif, 2026)
Since 2017, military operations in Myanmar, justified as responses to attacks by Rohingya insurgent groups, have resulted in large-scale ethnic cleansing, forcing over 700,000 Rohingya to flee to neighboring countries, including Indonesia. Aceh, in particular, has become a significant destination due to its historical role as a refuge for displaced populations. The influx of refugees presents substantial challenges for local authorities and humanitarian organizations in meeting essential needs such as food, healthcare, and education. The United Nations High Commissioner for Refugees (UNHCR) has played a central role in responding to this humanitarian crisis by providing assistance and protection to Rohingya refugees in Aceh. Working closely with the Government of Indonesia and local non-governmental organizations (NGOs), UNHCR strives to uphold refugees’ fundamental rights and to mobilize international support effectively. Its interventions include the provision of basic necessities, access to healthcare services, educational programs, and efforts to facilitate integration into the local community where feasible. Despite these comprehensive efforts, significant challenges persist. Coordination among various actors—including government agencies, NGOs, and international donors—is often complex, resulting in gaps or overlaps in service delivery. Additionally, the sustainability of support remains a critical concern, as protracted displacement requires long-term planning, continuous funding, and consistent monitoring. This study focuses on two main issues: the role of UNHCR in delivering assistance and protection to Rohingya refugees in Aceh, and the challenges the agency faces in fulfilling its protection mandate. Employing doctrinal legal research, the study emphasizes international legal frameworks governing refugee protection and state responsibility. The findings indicate that while UNHCR has made substantial efforts to address immediate humanitarian needs, persistent challenges in coordination and sustainability must be addressed. Strengthening these areas is essential to ensure that the protection, welfare, and rights of Rohingya refugees are maintained effectively and sustainably over the long term.